2022
DOI: 10.1002/mnfr.202200125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resveratrol Content in Red Wine on Circulating Sex Hormone‐Binding Globulin: Lessons from a Pilot Clinical Trial

Abstract: Scope: Low sex hormone-binding globulin (SHBG) levels are associated with higher risk of developing cardiovascular disease. Epidemiological studies have shown that red wine has beneficial effects on cardiovascular disease. In this work if resveratrol content in red wine increases SHBG levels is explored. Methods and results: A pilot study aims at testing the effect of drinking for 14 days two types of red wine with different resveratrol content is conducted in 26 healthy volunteers. SHBG levels and several bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Consequently, this cannot be considered as a negative effect of resveratrol intake. In any case, other authors did find a decrease in serum total cholesterol values [ 46 ] or a small increase [ 47 ] after nutritional interventions, even in healthy subjects, but it should be emphasized that the data, before and after resveratrol intervention, remained always within a range accepted as physiologic (200–220 mg/dL).…”
Section: Resultsmentioning
confidence: 79%
“…Consequently, this cannot be considered as a negative effect of resveratrol intake. In any case, other authors did find a decrease in serum total cholesterol values [ 46 ] or a small increase [ 47 ] after nutritional interventions, even in healthy subjects, but it should be emphasized that the data, before and after resveratrol intervention, remained always within a range accepted as physiologic (200–220 mg/dL).…”
Section: Resultsmentioning
confidence: 79%
“…Notably, moderate RW consumption did not alter the plasma mediators of inflammation in patients with T2DM [92]. No significant differences in fasting plasma glucose levels were revealed in a 14-day pilot study that compared two types of RW with different resveratrol contents [98]. Thus, no fasting glycaemic changes were detected in CAD [100] and hypercholesterolaemic [27] patients after ingesting RW.…”
Section: Body Composition Type 2 Diabetes and Glucose Metabolismmentioning
confidence: 82%
“…Accordingly, moderate wine consumption did not promote weight gain or abdominal adiposity in controlled diabetic patients following the Mediterranean diet [84], nor did fat accumulate in subcutaneous and abdominal fat depots in healthy subjects with a waist circumference above 94 cm [38]. A study that focused on two types of RW with different resveratrol content showed that the consumption of neither RW changed BMI [98]. Interestingly, healthy subjects consuming RW for 14 days displayed increased plasma levels of leptin, the main adipokine with the primary function of regulating energy balance, while no significant increase in plasma levels of adiponectin and other adipocytokines was observed [95].…”
Section: Body Composition Type 2 Diabetes and Glucose Metabolismmentioning
confidence: 95%
See 1 more Smart Citation
“…Evidence for a beneficial effect of increased SHGB in BC is also based on findings showing that SHGB reverses the anti-apoptotic effect of estradiol in BC cells, with a binding site on BC cells that has been shown to inhibit estradiol-induced cell proliferation after SHGB binding [224]. Indeed, other clinical studies have confirmed the modulatory effect of resveratrol on SHGB expression [225].…”
Section: Breast Cancermentioning
confidence: 99%